(untitled) (Contemporary Journal of Social Science Review, 2025)
In recent years, the design and construction of modern houses have evolved significantly, with a particular focus on the incorporation of open spaces. This comparative study aims to explore the differences between modern houses with and without open spaces, highlighting the advantages and disadvantages of each design approach. Modern houses with open spaces are known for their seamless integration of indoor and outdoor living areas. These homes often feature large windows, sliding glass doors, and spacious balconies or patios that blur the boundaries between the inside and outside. This design strategy creates a sense of openness and connectivity with nature, allowing residents to enjoy natural light, fresh air, and scenic views throughout the day. In conclusion, this comparative study highlights the significant impact that open spaces can have on the design and livability of modern houses. While both design approaches have their own unique advantages and disadvantages, it is clear that modern houses with open spaces offer a more dynamic, flexible, and enjoyable living experience for residents. By prioritizing the integration of open spaces into their designs, architects and homeowners can create modern houses that are not only beautiful and functional but also enriching and sustainable for years to come.